2000
DOI: 10.1353/hpu.2010.0590
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Health Care for Abused Latina and Asian Immigrant Women

Abstract: This study identifies social, political, and cultural barriers to help seeking from health care organizations faced by abused Latina and Asian immigrant women. Qualitative data were collected through four semistructured ethnic-specific focus group interviews with 28 abused Latina and Asian immigrant women. Participants who had suffered intimate partner abuse were recruited through urban community-based organizations in San Francisco, California. Sociopolitical barriers to help seeking and patient-provider comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
293
2
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(314 citation statements)
references
References 28 publications
11
293
2
8
Order By: Relevance
“…54,55 However, the high mortality rate of female IDUs in our cohorts also needs to be understood in light of the disproportional stigma the Hispanic culture holds against drug-using women. 56,57 Designing supportive systems, including health and drug treatment programs, that address the specific needs of Puerto Rican drug-using women should also become a high priority public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 However, the high mortality rate of female IDUs in our cohorts also needs to be understood in light of the disproportional stigma the Hispanic culture holds against drug-using women. 56,57 Designing supportive systems, including health and drug treatment programs, that address the specific needs of Puerto Rican drug-using women should also become a high priority public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that battered Latinas, especially those who are immigrants, are unlikely to utilize formal (Bauer et al, 2000;Dutton et al, 2000;Hogeland & Rosen, 1990;Krishnan et al, 1997;West et al, 1998) and informal help West, 1998) sources in order to survive abuse. For example, found that Latinas were least likely to contact a friend, minister, or social service agency.…”
Section: Ethnic Differences In Experiences Perceptions and Responsementioning
confidence: 99%
“…According to theory and research, culturally influenced gender roles, scripts, and values may significantly impact abused Latinas' (Bauer et al, 2000;Flores-Ortiz, 1994;Kanuha, 1994;King et. al, 1993;Martinez-Garcia, 1988;Perilla, 1999;Vera, 2002;Zambrano, 1985) and Mexican American women's (Avecedo, 2000;Morash, Bui, & Santiago, 2000;Sorenson, 1996;Torres, 1991) responses to abuse.…”
Section: Cultural Factors Associated With Mexican-origin Women's Respmentioning
confidence: 99%
See 2 more Smart Citations